The impact of the Covid- 19 crisis on family life in Saudi society: Descriptive study on a sample of families in Jeddah - Al- Nahdi, Sara Ibrahim; Al- Subhi, Roaa Hassan (Journal of Humanities & Social Sciences, 2022)
This study aimed at identify the impact of the Covid- 19 crisis on the interaction between spouses, on the self- development of family members, on recreational activities within the family, and to determine the relationship between the impact of the Covid- 19 crisis and a range of variables (type, social status, age, number of children, monthly income), and this study was applied to a sample of families in Jeddah, where the sample size (600) from couples. The approach used in the study was the social survey of the random sample in question, and the questionnaire was the data collection tool, and through the analysis of the study data the following results emerged: Covid- 19 had a positive impact on married couples at the center of interaction between spouses and the focus of recreational activities, the study also showed that the impact of the Covid- 19 crisis on the self- development of family members was somewhat positive, That there are statistically significant differences at the level (0.05) in recreational activities due to the difference in age variable for age groups under 40 years of age, and it was noted that females had a tendency towards self- development as well as recreational activities more than males during the Covid- 19 pandemic. The study recommends further studies dealing with crisis departments within the family, and their impact on the quality of family life, in the light of epidemic crises, to find more accurate results in order to create the era of crisis and the lack of research that deals with them from a social perspective, and to ensure that the family is educated and educated and activate its role in finding effective means and using all available resources to exploit the leisure time in the family.
Keywords: Covid-19; crisis; family life; Saudi society; impact